2015
DOI: 10.1002/art.39422
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use and Risk of Nonvertebral Fractures in Adults With Rheumatoid Arthritis: A Nested Case–Control Study Using Administrative Databases

Abstract: Among RA patients, the risk of nonvertebral fracture is increased in those treated with opioids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 46 publications
6
19
0
Order By: Relevance
“…Claims‐based studies indicate that the prevalence of opioid prescriptions for individuals with RA increased substantially in the late 1990s and early 2000s, with rates stabilizing in the mid‐2000s to mid‐2010s . While there is weak evidence that opioids are efficacious for the treatment of pain in RA , there is growing evidence that opioids are associated with serious risks, including nonvertebral fractures and serious infections . These observations highlight the importance of understanding the prevalence and predictors of chronic opioid use in RA.…”
Section: Introductionmentioning
confidence: 99%
“…Claims‐based studies indicate that the prevalence of opioid prescriptions for individuals with RA increased substantially in the late 1990s and early 2000s, with rates stabilizing in the mid‐2000s to mid‐2010s . While there is weak evidence that opioids are efficacious for the treatment of pain in RA , there is growing evidence that opioids are associated with serious risks, including nonvertebral fractures and serious infections . These observations highlight the importance of understanding the prevalence and predictors of chronic opioid use in RA.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed process of inclusion in this study is shown in Fig 1. Five studies were from the United States [12,21,23,24,26,32], three from Canada [9,19,28], two from the United Kingdom [18,27], one study was from Australia, and the remaining came from European countries; 12 articles were from cohort studies, and six were from case-control studies. The study information is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are two main mechanisms for the occurrence of fractures with opioid use. One mechanism is that opioids may reduce bone density by inhibiting the production of endogenous sex hormones, leading to an increased risk of fractures [34]; the other mechanism involves the side effects of opioids, such as the central nervous system side effects of vertigo, fatigue, etc., that lead to the occurrence of fractures [7,9,27,28], and there is a high incidence of side effects, including acute cognitive deterioration, increased sputum production, decreased oxygen saturation, and constipation, after the use of opioids in elderly populations, as confirmed in recent studies [35]. The trend of the population aging is becoming increasingly pronounced, and osteoporosis in this aging population is a serious concern.…”
Section: Discussionmentioning
confidence: 99%
“…Using predefined search strategies and inclusion criteria, a total of 18 studies were included and 1,134 articles of unrelated literature were excluded (from a total of 600 articles from PubMed and 552 articles from EMBASE) after a detailed reading of the title, abstract, and full text, and the 18 articles included 884054 participants [3,7,9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The detailed process of inclusion in this study is shown in Fig 1. Five studies were from the United States [12,21,23,24,26,32], three from Canada [9,19,28], two from the United Kingdom [18,27], one study was from Australia, and the remaining came from European countries; 12 articles were from cohort studies, and six were from case-control studies. The study information is shown in Table 1.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…In addition, there are two main mechanisms for the occurrence of fractures with opioid use. One mechanism is that opioids may reduce bone density by inhibiting the production of endogenous sex hormones, leading to an increased risk of fractures [34]; the other mechanism involves the side effects of opioids, such as the central nervous system side effects of vertigo, fatigue, etc., that lead to the occurrence of fractures [7,9,27,28], and there is a high incidence of side effects, https://doi.org/10.1371/journal.pone.0220216.g004…”
Section: Plos Onementioning
confidence: 99%